Outbound : finding a man, sailing an ocean - Storandt, William (University of Wisconsin Press, 2001)
Outbound is the story of two voyages: an Atlantic crossing in the 33-foot cutter Clarity, bound for Scotland; and the hard voyage of self-discovery that finally brought Bill Storandt to his life partner.